Future Dreams of Young People – Tools to Promote Young People’s Civic Participation - Katariina Heikkilä; Tuulia Nevala; Ira Ahokas; Liisa Hyttinen (Finland, 2022)
Do we hear the voice of children and young when developing our society? The research project “Young
people’s images of the future 2067” focuses on bringing forth youth’s dreams and hopes for the future,
and based on those desires to construct proposals for policymakers. A participatory future camp
method is used to challenge high school and vocational school students to ponder on future issues.
Based on future camp material a survey with six different futures images is designed and respondents
rate them according to probability and desirability. It is found out that the future camp method can be
used both for encouraging futures thinking and gathering data of future related values and thoughts.